Cytospora guizhouensis sp. nov., an endophytic fungus from Rosa roxburghii in Guizhou, China - Zhang, Hong; Jiang, Yu-Lan (Phytotaxa, 2025)
Rosa roxburghii, an economically significant medicinal and edible plant endemic to Southwestern China, particularly in Guizhou Province. In a survey of microfungi associated with R. roxburghii in China, three endophytic taxa were isolated from R. roxburghii. Phylogenetic analyses of concatenated LSU, ITS, rpb2, act, tef1, and tub2 sequence, combined with morphological characteristics, supported their classification as a novel species, Cytospora guizhouensis sp. nov. This taxonomic clarification establishes critical baseline data for further exploration of this endophytic resource’s biotechnological potential.